Comparative Transcriptomics Reveals Features and Possible Mechanisms of Glucose-Mediated Soil Fungistasis Relief in Arthrobotrys oligospora - Liu, Tong; Huang, Ying; Chen, Xiang-Xiang; Long, Xi; Yang, Yun-He; Zhu, Ming-Liang; Mo, Ming-He; Zhang, Ke-Qin (Frontiers in Microbiology, 2020)
Soil-borne pest diseases result in large annual agricultural losses globally. Fungal bio-control agents are an alternative means of controlling pest diseases; however, soil fungistasis limits the effect of fungal agents. Nutrients can relieve soil fungistasis, but the mechanisms behind this process remain poorly understood. In this study, we determined and quantified the transcriptomes of Arthrobotrys oligospora, a nematode-trapping fungus, derived from samples of fresh conidia, germinated conidia, soil fungistatic conidia, and glucose-relieved conidia. The transcriptomes of fungistatic and glucose-relieved conidia were significantly different from those of the other two conidia samples. KEGG pathway analyses showed that those genes upregulated in fungistatic and glucose-relieved conidia were mainly involved in translation and substance metabolism, and the downregulated genes were mainly involved in MAPK pathway, autophagy, mitophagy, and endocytosis. As being different from the transcriptome of fungistatic conidia, upregulated genes in the transcriptome of glucose-relieved conidia are also related to replication and repair, spliceosome, oxidative phosphorylation, autophagy, and degradation pathway (lysome, proteasome and RNA degradation). And the upregulated genes resulted from comparison of glucose-relieved conidia and fungistatic conidia were enriched in metabolic pathways, cycle, DNA replication and repair. The differentially splicing events in the transcriptome of glucose-relieved conidia are far more than that of other two transcriptomes, and genes regulated by differentially splicing were analyzed through KEGG pathway analysis. Furthermore, autophagy genes were proved to play important role in resisting soil fungistasis and glucose-mediated soil fungistasis relief. These data indicate that, in addition to being a carbon and energy source for conidia germination, glucose may also help to relieve soil fungistasis by activating many cellular processes, including autophagy, DNA replication and repair, RNA alternative splicing, and degradation pathways.